2005
DOI: 10.1590/s1806-83242005000200002
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and periodontal disease in diabetic pregnant women

Abstract: ABSTRACT:This cross-sectional study investigated the impact of pregestational overweight and obesity on periodontal status of patients with gestational diabetes mellitus (GDM). Sixty pregnant women with gestational diabetes mellitus (GDM) were recruited for the study. According to the pregestational body mass index (BMI), patients were classified into 3 groups: normal, overweight or obese. The periodontal assessment parameters were the presence of gingival bleeding (GB) and bleeding on probing (BOP) per tooth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 20 publications
1
32
2
4
Order By: Relevance
“…Obesity (defined as BMI >29 kg/m 2 ) was not associated with periodontal disease in this study 45 . All three of these studies were conducted in Brazil 43‐45 . The design of all these studies was cross‐sectional; thus, it is difficult to determine the temporal relationship between obesity and periodontal disease 43‐45 .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Obesity (defined as BMI >29 kg/m 2 ) was not associated with periodontal disease in this study 45 . All three of these studies were conducted in Brazil 43‐45 . The design of all these studies was cross‐sectional; thus, it is difficult to determine the temporal relationship between obesity and periodontal disease 43‐45 .…”
Section: Discussionmentioning
confidence: 86%
“…However, they did not mention any adjustment for GDM 43 . Chapper et al 44 recruited 60 non‐smoking pregnant females with GDM in a cross‐sectional study in Brazil, and they reported that females with pregestational obesity had significantly more gingivitis and periodontal attachment loss compared with those with normal BMI. However, the authors did not explicitly define periodontal disease 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies have reported a positive association between excessive weight and periodontitis during pregnancy. Nonetheless, these studies used different methodologies for the classification of periodontitis and nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…[21] Women with pre-gestational overweight/obesity had significantly more periodontal attachment loss & gingivitis compared with those with normal ƁΜӀ. [88] A cross-sectional study applied to evaluate factors associated with periodontitis, they found that the odds of having periodontitis in pregnant women who were overweight/obese before pregnancy was 2.22 times the odds in pregnant women with normal weight. [89] The risk of Periodontitis increases by l6% per increase of 1 kg/m 2 in ƁΜӀ.…”
Section: Discussionmentioning
confidence: 99%